BMP2 transfer to neighboring cells and activation of signaling - Alborzinia, Hamed; Shaikhkarami, Marjan; Hortschansky, Peter; Wölfl, Stefan (Traffic, 2016)
Morphogen gradients and concentration are critical features during early embryonic development and cellular differentiation. Previously we reported the preparation of biologically active, fluorescently labeled BMP2 and quantitatively analyzed their binding to the cell surface and followed BMP2 endocytosis over time on the level of single endosomes. Here we show that this internalized BMP2 can be transferred to neighboring cells and, moreover, also activates downstream BMP signaling in adjacent cells, indicated by Smad1/5/8 phosphorylation and activation of the downstream target gene id1. Using a 3D matrix to modulate cell-cell contacts in culture we could show that direct cell-cell contact significantly increased BMP2 transfer. Using inhibitors of vesicular transport, transfer was strongly inhibited. Interestingly, cotreatment with the physiological BMP inhibitor Noggin increased BMP2 uptake and transfer, albeit activation of Smad signaling in neighboring cells was completely suppressed. Our findings present a novel and interesting mechanism by which morphogens such as BMP2 can be transferred between cells and how this is modulated by BMP antagonists such as Noggin, and how this influences activation of Smad signaling by BMP2 in neighboring cells.
Gesehen am 13.08.2020